1999
DOI: 10.1159/000069413
|View full text |Cite
|
Sign up to set email alerts
|

Physical Trauma and Family History of Neurodegenerative Diseases in Amyotrophic Lateral Sclerosis: A Population-Based Case-Control Study

Abstract: This population-based case-control study was conducted in three counties in western Washington state (USA) between 1990 and 1994 to assess the association between amyotrophic lateral sclerosis (ALS) and several hypothesized risk factors, including a family history of neurodegenerative diseases, physical trauma (fractures, electrical shocks, and surgeries), rural residence, travel, and medical history. One hundred seventy-four cases with ALS, newly diagnosed by neurologists, were identified through several case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 30 publications
5
55
1
1
Order By: Relevance
“…The relationship between exposure to pesticides, agricultural occupations and residing in a rural area and risk of ALS has been inconsistent as only about half of the epidemiologic studies, including two meta-analyses, have found an association [14,20,21,22,23,24,25]. However, this finding has not been replicated by some studies [26,27,28,29]. The association of occupational electromagnetic field exposure with ALS has also been investigated, with most published reports indicating a positive relationship [30].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between exposure to pesticides, agricultural occupations and residing in a rural area and risk of ALS has been inconsistent as only about half of the epidemiologic studies, including two meta-analyses, have found an association [14,20,21,22,23,24,25]. However, this finding has not been replicated by some studies [26,27,28,29]. The association of occupational electromagnetic field exposure with ALS has also been investigated, with most published reports indicating a positive relationship [30].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that between 5-10% of ALS cases are familial (and not sporadic) in origin; 18,21 in line with this, 4.3% of our case series had a blood relative with ALS. Similarly, in Cruz et al, 22 5.2% of patients had a blood relative with ALS; their cases were significantly more likely to have blood relatives with ALS than were controls.…”
Section: Family Medical Historymentioning
confidence: 73%
“…However, in their study of physical trauma and family history of neurological disease, Cruz et al 22 found that 4.6% and 2.3% of their cases' firstdegree relatives had Alzheimer's and Parkinson's disease, respectively; their cases were no different from controls. The percentages of our cases reporting family members with these neurological diseases were somewhat higher, with 8.6% reporting a first-degree relative with Alzheimer's disease and 4.3% reporting a first-degree relative with Parkinson's disease.…”
Section: Family Medical Historymentioning
confidence: 93%
See 2 more Smart Citations